Correlation of Serum Vitamin B12 and Iron as etiologic factors in recurrent aphthous stomatitis: A case-control study - Thalamalai Saravanan; Subha Manoharan; C Saravana Bharathi; K R Shakila (Wolters Kluwer Medknow Publications, 2021)
Objective: This study aimed to estimate and correlate the levels of serum vitamin B12, iron, and their association with family history and cigarette smoking in patients with recurrent aphthous stomatitis (RAS). Methods: Sample size was calculated using the earlier prevalence studies with a power of 85% and rounded to 30 considering other confounding factors. Thirty patients with RAS and 30 control subjects were included in this controlled prospective study. A proforma on demographic details and case history was filled followed by serum analysis for Iron and B12. The collected data were analyzed using SPSS 20. Results: Family history is a significant predisposing factor for RAS. Vitamin B12 was found to have a significant positive correlation with RAS. Patients with vitamin B12 deficiency, positive family history, and nonsmoking status have been found to have the highest risk for having RAS. Binary logistic regression analysis revealed a significant relationship between vitamin B12 and RAS (probability P =0.001). Conclusion: Our study had shown a positive correlation of RAS with family history and vitamin B12 deficiency.